Pharmacy technician knowledge and behavior regarding high alert drugs - Muhajri Agusfina; Renatalia Fika; Mevy Trisna; Desy Kurniaty; Zulfisa Zulfisa (Science Midwifery, 2026)
High Alert is a drug that often causes serious errors (sentinel event). This drug is very high risk and can cause unwanted impacts (adverse outcomes), therefore it is necessary to supervise its use. The purpose of this study was to determine the level of knowledge of pharmacy vocational staff about the management of high alert drugs at the Pharmacy Installation of X Hospital in Dumai City and to describe the relationship between knowledge and behavior of pharmacy vocational staff about the management of high alert drugs at the Pharmacy Installation of X Hospital in Dumai City. The research   was conducted using non-experimental observational methods with a cross-sectional analytic approach with questionnaire data design. The population in this study were all pharmacy vocational staff at the Pharmacy Installation of X Hospital in Dumai City, totaling 23 people. The sample used was using total sampling technique. The validity and reliability values obtained by researchers about knowledge and behavior statements are declared valid if the r count and the value of Person Croanch's Alpha obtained> 0.630. Based on the questionnaire, it is declared reliable because the value of Person Cronch's Alpha for knowledge is 0.702 and behavior is 0.891> 0.630.  Based on the results of the research conducted, it can be concluded that there is no relationship between the knowledge and behavior of pharmacy vocational staff in managing high alert drugs at X Hospital in Dumai City with a significance value> 0.005 p = value 1.028. This study shows that there is no relationship between knowledge and behavior.